Risks and opportunities of trophic rewilding for arthropod communities - van Klink, Roel (Philos Trans R Soc Lond B Biol Sci, 2018)
Trophic rewilding is a restoration strategy focusing on the restoration of trophic interactions to promote self-regulating, biodiverse ecosystems. It has been proposed as an alternative to traditional conservation management in abandoned or defaunated areas. Arthropods constitute the most species-rich group of eukaryotic organisms, but are rarely considered in rewilding. Here, we first present an overview of direct and indirect pathways by which large herbivores and predators affect arthropod communities. We then review the published evidence of the impacts of rewilding with large herbivores on arthropods, including grey literature. We find that systematic monitoring is rare and that a comparison with a relevant control treatment is usually lacking. Nevertheless, the available data suggest that when the important process of top-down control of large-herbivore populations is missing, arthropod diversity tends to decrease. To ensure that rewilding is supportive of biodiversity conservation, we propose that if natural processes can only partially be restored, substitutes for missing processes are applied. We also propose that boundaries of acceptable outcomes of rewilding actions should be defined a priori, particularly concerning biodiversity conservation, and that action is taken when these boundaries are transgressed. To evaluate the success of rewilding for biodiversity, monitoring of arthropod communities should be a key instrument. This article is part of the theme issue ‘Trophic rewilding: consequences for ecosystems under global change’.